Vývoj fauny obratlovců v severočeských pískovcových územích během holocénu - Horáček, I.; Sázelová, S. (Sandra) (2017)
The comprehensive information about the history of the Late glacier and Early Holocene environment specifically extends the results based on the vertebrate fossil record analyzes. In total, vertebrates from 123 North Bohemian sandstone sites (with the richest records from the Bohemian Paradise and Českolipsko region) belonging to 1078 individuals of 60 species were documented. The comparison of the species spectrum demonstrates a radical transformation in vertebrate communities - from the glacial elements living in the open steppe and tundra landscape, through the forest species with high diversity in the Early Holocene to the changes within the Neolithic landscape due to the large-scale deforestation, invasion of the cultural steppe communities, etc.